1991
DOI: 10.1002/1097-0142(19910315)67:6<1614::aid-cncr2820670624>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Human immunodeficiency virus‐associated Hodgkin's disease. Clinicopathologic studies of 24 cases and preponderance of mixed cellularity type characterized by the occurrence of fibrohistiocytoid stromal cells

Abstract: Hodgkin's disease (HD) was diagnosed in 24 patients who were either seropositive for human immunodeficiency virus (HIV) (21) or members of a high-risk group (three), but had not developed acquired immune deficiency syndrome (AIDS). Clinical presentation of the disease was characterized by constitutional symptoms in all, especially fever (23/24) and disseminated disease (22/24) at diagnosis. Mediastinal adenopathy was rare. Bone marrow involvement was particularly frequent (12/24), and a positive bone marrow bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0
3

Year Published

1992
1992
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(19 citation statements)
references
References 28 publications
3
13
0
3
Order By: Relevance
“…27 The CD30 ϩ , CD45 Ϫ , CD15 ϩ , EMA Ϫ phenotypic profile was required for the diagnosis of classic HL. 22 The Rye modification of the Lukes and Butler [28][29][30] classification was used to classify the histologic subtypes of classic HL.…”
Section: Neoplastic Samplesmentioning
confidence: 99%
“…27 The CD30 ϩ , CD45 Ϫ , CD15 ϩ , EMA Ϫ phenotypic profile was required for the diagnosis of classic HL. 22 The Rye modification of the Lukes and Butler [28][29][30] classification was used to classify the histologic subtypes of classic HL.…”
Section: Neoplastic Samplesmentioning
confidence: 99%
“…The nodular pattern of involvement in some patients in our series raised differential diagnoses either with reactive polymorphous lymphohistiocytic lesions, a common feature in patients with immune disorders including HIV infection (18), and with other lymphoid neoplasms: the identification of classic Reed-Sternberg cells with the appropriate phenotype appeared critical in reaching a correct diagnosis and in excluding peripheral T-cell lymphomas, T-cell-rich large B-cell lymphomas, and lymphocytic-predominance HL. The lack of immunoreactivity of Reed-Sternberg cells for the immunoglobulin gene transcription regulator molecule Oct2 is similar to that observed in the majority of classical HIV-unrelated HL (10).…”
Section: Discussionmentioning
confidence: 78%
“…In addition, single cases from small series showing features potentially similar to IBM-HIV-HL as defined in the present study have been reported (17,18), although selection criteria were not clearly specified. All cases hereby reported were diagnosed on the basis of detection of classical ReedSternberg cells with typical immunophenotype in the bone marrow; furthermore, strict selection criteria for isolated bone marrow involvement were adopted, and the single patient (Case 2) who, despite the lack of clinically evident lymphadenopathy, underwent a lymph node biopsy failed to show nodal HL.…”
Section: Discussionmentioning
confidence: 93%
“…However the most frequent subytype in HIV patients comprises the most unfavorable variants such as mixed cellularity and depletion of lymphocytes of the clasical HL(p<0.01), other features published are the abundance of a proliferation of the fibrohistiocyte stroma and a higher perecentage of Reed-Sternberg cells (Ree et al 1991;Bellas et al 1996). Relation between EBV infection and the origin of LH seems to be tighter in HIV infected patients than in the reamainder LH cases (Ree et al 1991). The combined use of in situ hybridation techniques, immunohistochemistry to determine the expression of LMP-1, indicative of latent EBV infection, and other molecular biology techniques have demonstrated that 78 to 100% of HIV+HL cases are associated to the EBV.…”
Section: Hodgkin Lymphomamentioning
confidence: 99%